Impacts of COVID-19 on Nepalese economy - Devkota, Satis (Applied Science and Technology Annals, 2020)
Even though Nepal reported the first confirmed case of COVID-19 in late January 2020, Nepal was one of the least affected countries in South Asia until the end of April 2020. Lockdown and social distancing were implemented from the very beginning and people also contributed voluntarily with certain exceptions to that government’s efforts. That has a positive effect on flattening the curves of COVID-19 affected people and the related death rates in Nepal. However, the macroeconomic consequences of the pandemic are pretty high for a remittance based small economy. This hardship is further escalated when the excessive inflow of the Nepali migrant workers from India carried and transmitted the virus to 1,811 people by June 1, 2020. Still, that number is not high if the government gets success to control the spread outright.